2017
DOI: 10.1210/jc.2017-00612
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Anti-Müllerian Hormone Variants in Polycystic Ovary Syndrome

Abstract: To our knowledge, this study is the first to identify rare genetic variants associated with a common PCOS phenotype. Our findings suggest decreased AMH signaling as a mechanism for the pathogenesis of PCOS. AMH decreases androgen biosynthesis by inhibiting CYP17 activity; a potential mechanism of action for AMH variants in PCOS, therefore, is to increase androgen biosynthesis due to decreased AMH-mediated inhibition of CYP17 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 46 publications
3
46
0
1
Order By: Relevance
“…Collectively, these results make BMPR1B a 477 compelling candidate gene in PCOS pathogenesis. These findings also support our 478 sequencing studies that have implicated pathogenic variants in the AMH signaling pathway 479 in PCOS (61,62). 480…”
Section: Subtypes In Pcos Families 398supporting
confidence: 67%
“…Collectively, these results make BMPR1B a 477 compelling candidate gene in PCOS pathogenesis. These findings also support our 478 sequencing studies that have implicated pathogenic variants in the AMH signaling pathway 479 in PCOS (61,62). 480…”
Section: Subtypes In Pcos Families 398supporting
confidence: 67%
“…PCOS is strongly familial [14][15][16] and highly heritable [17], with~60% of daughters born to women with PCOS manifesting their own PCOS phenotype during adolescence and young adulthood [18]. Mounting evidence suggests, however, that heritable defects leading to ovarian hyperandrogenism contribute to the manifestation of PCOS [19].…”
Section: Pcos and Its Potential Originsmentioning
confidence: 99%
“…Gorsic et al . found that 18 rare AMH variants are specific to women with PCOS and that 17 of them significantly reduce AMH signaling . On the other hand, Wang et al .…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%